Gender as a Predictor of Complications in Endoscopic Sinus Surgery. (August 2021) - Sharma, Rahul K.; Dodhia, Sonam; Golub, Justin S.; Overdevest, Jonathan B.; Gudis, David A.
Background: Understanding patient-specific risk factors for complications of functional endoscopic sinus surgery (ESS) is critical. Previous work has investigated such risk factors, but a population-based analysis has not been performed to date. Objectives: This study analyzes the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database to identify patient-specific risk factors associated with complications following ESS. Methods: A retrospective cohort study of patients who underwent ESS was conducted using the NSQIP database from 2011 to 2017. Patients were identified using CPT-codes for ESS procedures. The primary outcome analyzed was any postoperative complication. Simultaneous procedures with ESS were controlled for with regression analysis. Post-operative complications and 30-day readmission were evaluated using multivariate logistic regression controlling for age, gender, race, comorbidities (diabetes mellitus, hypertension, chronic obstructive pulmonary disease, congestive heart failure, renal failure, steroid use, and cancer history), smoking history, and intraoperative factors. Results: A total of 1279 patients who underwent ESS were identified. The average age of patients was 46.1 (SD = 16.8). Most patients (58.2%) had no major comorbidities. 594 (46.4%) patients had a tonsillectomy, adenoidectomy, or uvulopharyngoplasty at the same time as ESS. 101 (7.9%) patients experienced a complication post-operatively. 46 (3.6%) patients experienced a readmission postoperatively. The most common complication was reoperation (N = 40, 3.1%). Regression analysis revealed that gender was the only demographic factor associated with risk of post-operative complications, with women having a significantly lower risk than men (OR = 0.61, 95% CI 0.37-0.99, P = .046). Conclusions: ESS is typically performed on a relatively young and healthy population. Women have a significantly lower risk of complications after controlling for comorbidities. Further analysis of gender-specific differences in surgical outcomes should be evaluated to understand this phenomenon.